Lung Diffusion Capacity of X Fighter Pilot in Madiun - Ririn Astuty Ningsih; Faisal Yunus; Triya Damayanti; Flora Ekasari; Sita Laksmi Andarini; Dicky Soehardiman; Ratnawati Ratnawati; Fathiyah Isbaniah; Erlang Samoedro (Jurnal Respirologi Indonesia, 2020)
Background: Pilot works in the high environment that exposed by G force. Increasing G force led to linear decreases in cardiac output and blood oxygenation of the brain. Thus, likely due to decreased lung gas exchange capacity in hypergravity. This study aims to investigate the pulmonary diffusing capacity test among Fighter pilots in Madiun. Methods: This study used cross sectional method conducted on February 2019 in Madiun. The total subjects consist of 44 Fighter pilots based on total sampling. Interview was done to fill out question about sociodemografic and smoking habit, flight hour data and physical fitness. Lung function measurement was done using portable spirometry and DLCO equipment (Easyone TM Pro Lab). Result: Spirometri result was found in the standard normal range in 41 subjects (93,2%) only 3 subject (6,8%) get obstruction abnormalities and none of them get restriction result. Average VEP1 prediction was 103,3±10,60 % and median range for VEP1/KVP was 84,5(63,5-92,5) %. Lung diffusion capacity measurement was found to be normal in 41 subject (93,2%) and to be deficient in 3 subject (6,8%) in smoker. Conclusion: This study demosntrated that diffusion capacity and spirometry test in Fighter pilots generally in normal range. Lung diffusion capacity has no association with age, BMI, flight hour, physical fitness, Brinkman index and spirometry parameters. (J Respir Indo. 2020; 40(1): 39-47)